Examining the Correlation between Parental Expectations and Parental Participation: A Meta-Analysis - Solichah, Novia; Fardana, Nur Ainy; Samian, Samian; Muhid, Abdul (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
Parental expectations play a role in shaping parental involvement, potentially leading to positive outcomes for children. Despite the importance of these factors, research on parental expectations and involvement has been limited in the past two decades. Therefore, this study aims to explore the connection between parental expectations and involvement through a meta-analysis. Following the PRISMA guidelines, we conducted a thorough analysis of existing literature. Employing a meta-analytical approach, data were collected from ten reputable international journal databases, including Scopus, SAGE, Emerald, Web of Science, Proquest, PubMed, Taylor and Francis, Google Scholar, Springer, and Science Direct. The inclusion criteria focused on research centered on parental expectations and parental involvement, resulting in eight articles included in our final analysis. The evaluation of quality employed the Appraisal Tool for Cross-Sectional Studies (AXIS) to gauge bias risk. Results indicate a noteworthy correlation between parental expectations and involvement (r=0.209, p0.001), implying that higher parental expectations correlate with greater parental involvement and vice versa. Moreover, our analysis revealed high heterogeneity (I2 = 96.44%) among the studies, indicating substantial variability. Additionally, the bias assessment (p = 0.048) indicated evidence of publication bias across the studies. Future research opportunities lie in developing studies that delve into the association between parental expectation and parental involvement, examining how this relationship functions independently from other variables in specific contexts such as student achievements or early literacy.